The Significance of Genetic Relatedness and Nest Sharing on the Worker‐Worker Similarity of Gut Bacterial Microbiome and Cuticular Hydrocarbon Profile in a Sweat Bee - Federico Ronchetti; Thomas Schmitt; Alexander Keller; Andrés García‐Reina; Pilar De la Rua; Ingolf Steffan‐Dewenter; Carlo Polidori (Ecology and Evolution, 2025)
ABSTRACT The cuticular hydrocarbon (CHC) profile and the gut microbiome (GM) are crucial traits which have a significant impact on the life of bees. In honey bees, the CHC profile and the GM interact finely through trophallaxis, such that the characteristics of the GM are partially defined by the chemical recognition among sisters. However, most of the known primitively eusocial bees show simpler social traits, including moderate genetic relatedness among colony members, often due to workers' nest drifting or dispersal, and lack of trophallaxis. Hence, primitively eusocial bees offer a great opportunity to evaluate the respective role of worker‐worker genetic relatedness and of the environment in which the adult lives (residency nest) on the interaction between CHC profile and GM. Here, we investigated such relationships in the primitively eusocial digger bee Halictus scabiosae (Halictidae). We found a high rate of nest‐drifting by workers, which leads to a consequent highly variable intra‐colonial genetic relatedness. Genetically closely related workers, even occupying distant nests, did possess both a more similar microbiome profile and a more similar CHC profile. Additionally, sharing the same nest seemed to account for the similarity of both CHC profile and GM among workers. Interestingly, differences in microbiome profile and in CHC profile were highly and positively correlated across workers, even after controlling for genetic relatedness. The results of our study point towards an impact of genetic relatedness on the GM and the CHC profile, but also suggest that microbiome and CHC profile are partially acquired through adult nest environment, and that microbiome possibly has a role in shaping the cuticular chemistry.